Multi-omic analysis reveals that Bacillus licheniformis enhances pekin ducks growth performance via lipid metabolism regulation - Li, Lei; Yang, Liangyu; Zhang, Limei; He, Fengping; Xia, Zhaofei; Xiang, Bin (Frontiers in Pharmacology, 2024)
Background Bacillus licheniformis was widely used in poultry feeds. The experiment was designed to clarify the effect and molecular mechanism of Bacillus licheniformis on the lipid metabolism and developmental growth of Pekin ducks through multiomics analysis, including transcriptomic and metabolomic analyses.The results showed that compared with the control group, the addition of 400mg/kg Bacillus licheniformis ( B.licheniformis) could significantly increase the body weight of Pekin ducks and the content of TG (P＜0.05), at the same time, the addition of B.licheniformis could affect the lipid metabolism of liver in Pekin ducks, and the addition of 400 mg/kg B.licheniformis could significantly increase the content of LPL in liver of Pekin ducks. We found that B.licheniformis effectively influences fat content and lipid metabolism by modulating lipid metabolism-associated enzymes in the liver. Transcriptomic analysis revealed that the addition of B.licheniformis primarily impacted fatty acid and glutathione, amino acid metabolism, fatty acid degradation, as well as biosynthesis and elongation of unsaturated fatty acids. Metabolomic analysis indicated that B.licheniformis primarily affected the regulation of glycerol phospholipids, fatty acids, and glycerol metabolites. Multiomics analysis demonstrated that the addition of B.licheniformis to the diet of Pekin ducks enhanced the regulation of enzymes involved in fat synthesis via the PPAR signaling pathway, actively participating in fat synthesis and fatty acid transport. These results shed light on the potential molecular mechanisms by which B.licheniformis regulates fat metabolism. Ultimately, this study contributes to our understanding of how B.licheniformis can improve the growth performance of Pekin ducks, particularly in terms of fat deposition, thereby providing a theoretical foundation for its practical application. Conclusions B.licheniformis can increase the regulation of enzymes related to fat synthesis through PPAR signal pathway, and actively participate in liver fat synthesis and fatty acid transport, thus changing the lipid metabolism of Pekin ducks, mainly in the regulation of glycerol phospholipids, fatty acids and glycerol lipid metabolites.